Unfolding the practical knowledge of an expert strength and conditioning coach - Dorgo, S. (International Journal of Sports Science and Coaching, 2009)
To define the professional knowledge base used in practice, the purpose of this study was to reveal the content of practical knowledge of an expert strength and conditioning coach. A qualitative case study design was used. The participating coach met a list of criteria typically associated with expert coaches. Data collection included observations, interviews, and document analyses. Following the data analysis, ten major knowledge categories emerged, which were separated into the Foundational Practical Knowledge and Applied Practical Knowledge clusters. It appeared that the participant`s set of practical knowledge was structured in several layers and was only partially built on the Foundational Disciplinary Knowledge originating from formal education. Analysis suggested that most aspects of the participant`s practical knowledge were developed through field experience, real-life practices, and other professionals. The present study suggests that coaching educational programs should be expanded and modified to reflect all aspects of knowledge used in practice.